Оценка результатов лечения пациентов с паховой грыжей методом тотальной экстраперитонеоскопической герниопластики - Клименко, А. В.; Белай, А. И.; Клименко, В. Н.; Klymenko, A. V.; Bilai, A. I.; Klymenko, V. N.; Клименко, Андрій Володимирович; Білай, Андрій Іванович; Клименко, Володимир Микитович (My University, 2016)
The frequency of hernia repair in the surgical hospital makes up 10-25% of all surgical interventions and is the second most common surgery in the world. Among the abdominal wall hernias inguinal ones, which make up 65-80% of the total are the most common. More than 400 ways of inguinal hernias plasty have been developed, but despite this, the number of postoperative complications and patients’ life quality are the problems of modern herniology. Considering the socio-economic aspects endoscopic methods of plasty are more preferable. Rational choice of the method of inguinal hernia plasty remains urgent and requires rational approach to solving this problem. The purpose of this work was to improve the results of inguinal hernias treatment by applying total extraperitoneoscopic hernioplasty (TEP-repair). The analysis of the treatment of 67 patients with the implementation of TEP-repair has been made. An algorithm of diagnosis and the choice of operation method for patients with unilateral and bilateral inguinal hernia has been elaborated. The proposed technique with the use of non-fixed polypropylene mesh implant is characterized by the absence of chronic pain syndrome in the near and long-term periods, favourable immediate results without lethal outcomes and with minimal number of complications. In the long-term period there are no recurrences of inguinal hernia, no complications on the side of the adjacent organs. High indices of life quality according to special questionnaire Eura HS-QoL data have been noted.
The evaluation of the treatment results of the patients with inguinal hernia by the method of extraperitoneoscopic hernioplasty
Keywords: паховая грыжа; герниопластика; хирургическое лечение; inguinal hernia; hernioplasty; surgical treatment